Optical and surface properties of 3C–SiC thin epitaxial films grown at different temperatures on 4H–SiC substrates. (August 2021) - Wang, Bingjun; Yin, Junhua; Chen, Daihua; Long, Xianjian; Li, Lei; Lin, Hao-Hsiung; Hu, Weiguo; Talwar, Devki N.; Jia, Ren-Xu; Zhang, Yu-Ming; Ferguson, Ian T.; Sun, Wenhong; et al.
Abstract: A series of 3C–SiC films were grown on 4H–SiC substrates with different growth conditions using high-temperature chemical vapor deposition (HT-CVD). The influences of growth temperature (Tg) on the morphology, optical and material properties of films were assessed by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and Raman scattering spectroscopy (RSS). Significant effects of Tg on the film crystalline quality were observed from analyzing XRD and RSS results. XPS characterized the surface states of Si, C, O elements, and variations with Tg. The 3C–SiC Raman TO mode was found to shift to lower frequency with the increase of Tg in 1530–1580 °C. Temperature dependent Raman studies indicated the anharmonic coupling and variation of phonon lifetimes. The optimized Tg is obtained. Highlights: XRD/XPS/Raman: 3C/4H-SiC films. Quantified defects- depth variation. Optimized growth temperature. HT phonon coupling.